Infertility study of Boswellia Serrata: a wild Ethnomedicinal plant for Therapeutic purpose by In Silico Study - PATEL NIKUNJ B., (International Journal of Pharma and Bio Sciences, 2019)
In biomedical field, in silico design is being developed to advance and easy hit identification, hit-to-lead selection, optimize absorption, distribution, metabolism, excretion and toxicity Generally computational approaches utilized comprise ligand-based drug design, structure-based drug design, and quantitative structure-activity and quantitative structure-property relationships. There are more than a hundred chemical compounds that derived from medicinal plants for use as drugs and medicines. Boswellia serrata Roxb. ex Colebr. is a deciduous tree of the Burseraceae family and native to India and Pakistan. It is same as to botanical Burseraceae family as the tree from which myrrh is harvested. In India, frankincense from the tree is also called "salai guggal." The gum oleoresin consists of essential oils, gum, and terpenoids. The terpenoid portion contains the boswellic acids that have been shown to be the active constituents in Boswellia. Nowadays, extracts are typically standardized to contain 37.5–65% boswellic acids. Medicinal plants having chemical compounds belonging to successful target (Cytochrome P450 19 for Male Infertility). The medicinal plant containing natural and it’s synthesized chemical compounds were also examined for drug-likeness. Molecular docking studies were also carried out. The virtual screening of ligand library to the best score and to binding site of the ligand 2-ethenyl-6-methylhept-5-en-1-yl acetate with the successful target from the ligand library included in the study. The result points out ligand CID: 109340 as best from the library for further study. Synthesized chemical compounds have best score comparison to the natural chemical compound present in the Boswellia serrate Roxb. Ex Colebr wild medicinal plant.